If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y + 2 = 40 Reorder the terms: 2 + Y = 40 Solving 2 + Y = 40 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + Y = 40 + -2 Combine like terms: 2 + -2 = 0 0 + Y = 40 + -2 Y = 40 + -2 Combine like terms: 40 + -2 = 38 Y = 38 Simplifying Y = 38
| 4e^5x=644 | | 3-(2x-8)= | | 5x-2x-9=3x-17 | | 36-a=36 | | 3x+25=28 | | 7e^8x=1015 | | 3e^7x=756 | | d(x)=0.04x^2+2x | | 7y-34+9x-4=180 | | 0.6(2.4a-1.4)=6 | | 6(x-1)-4=14 | | 3y+7=3y-12 | | 12-.5x=7 | | (34+13i)-(-2-17i)+(16+25i)=0 | | x+10y=-8 | | 7+m=20 | | p^2=6p+16 | | 8(t+8)=96 | | 9y+28=120 | | 3(5x+2)=8x-5 | | -1+2x=-7 | | 3x+7y-21=10xy+(-21) | | 5.75x-10=9.25+2 | | -6.1n-3.9n= | | 13y=4y+36 | | 13.50/20= | | 10y+4=124 | | 36=3(x+6) | | 9x^2-6x+k=0 | | i(3+2i)(3+2i)=0 | | 15+n=15 | | 5n+4x=3v |